Travel in Islam (A Study of the Concept of Sīrū in the Qur’an) - Hamim, Khairul (Ulumuna, 2023)
This paper analyzes the command to travel in the Qur’an, which is understood from the word sīrū or yasīrū with various accompanying words. The Quranic injunction to travel that uses the word sīrū contains orders to contemplate, think, and take lessons from the attitude of the former people who denied the Prophet and Messenger of Allah and the consequences experienced by these people. Productive tourism in the Qur’an is carried out with a good purpose, benefiting oneself, others, and the surrounding environment and maximizing the use of reason, mind, and heart. In the Qur’an, the orientation of travel is very varied, namely, seeing the behavior of the former people, knowing the universe and its contents, adding insight, clearing the heart, softening the mind, and so on. The phenomenon of travel and efforts to develop the tourism sector in various countries are currently very diverse and continue to develop significantly in various means and forms so that they can provide benefits for social, political, cultural, and religious life. The order to travel contained in the word sīrū must be actualized in today’s modern life by sticking to and being guided by the values ​​in the holy book of the Qur’an.